Monitoring of serum magnesium levels during long-term use of proton pump inhibitors in elderly japanese patients: is it really necessary or not? - Nobuhiko Nakamura; Kanaha Yoneda; Takashi Higo; Masaaki Kusumoto (BMC, 2022)
Abstract Background Long-term use of proton pump inhibitors (PPIs) has been found to significantly lower serum magnesium levels in patients in the USA and Europe. The package inserts of PPIs in these countries clearly state that healthcare professionals should consider monitoring magnesium levels prior to initiation of PPI treatment and periodically thereafter. However, the package inserts of PPIs in Japan do not clearly mention the monitoring of magnesium levels. In this study, we evaluated the relationship between long-term use of PPIs and the lower serum magnesium concentrations in elderly Japanese patients. Methods Using a retrospective observational approach, a total of 264 Japanese outpatients were included in the study. Patients over the age of 75 years were considered elderly. Serum magnesium levels of the patients were measured in units of 0.1 mg/dL between January 2016 and June 2022 at the Higo Internal Medicine Clinic and Ai Pharmacy in Kyoto, Japan. Results Four of the 264 eligible patients were diagnosed with hypomagnesemia. Three were PPI non-users, and one was a PPI user. Serum magnesium concentrations were significantly lower in PPI users (n = 47) than in non-users (n = 85; 2.1 ± 0.2 vs. 2.2 ± 0.3 mg/dL, p < 0.05) in the 132 elderly patients. Comorbidity included diabetes mellitus in both PPI users (23.4%) and non-users (57.6%) and hyperlipidemia in both PPI users (61.7%) and non-users (41.2%). Conclusion PPIs are commonly used oral drugs for elderly patients. There was an association between the long-term use of PPIs and lower serum magnesium concentrations in elderly patients. Although the difference in the decrease in serum magnesium concentrations was within the normal range of serum magnesium levels, health care professionals should consider monitoring serum magnesium levels periodically in elderly patients receiving long-term PPIs.